A note on movements of southern right whales between the sub-Antarctic Auckland and Campbell Islands, New Zealand - Patenaude, Nathalie J.; Todd, Barbara; Stewart, Ramari (J. Cetacean Res. Manage., 2020)
To investigate the interchange of southern right whales between wintering grounds of the New Zealand sub-Antarctic, photographs of 31 individuals from Campbell Island were compared to 217 individuals from the Auckland Islands. Three whales first identified at the Auckland Islands in 1995 or 1996 were found at Campbell Island in 1997. One whale identified at Campbell Island in 1995 was seen later that same winter at the Auckland Islands. This provides the first evidence of both within- and between-year movements of whales between the two New Zealand sub-Antarctic aggregations, suggesting that they are part of one intermingling population.